Feasibility of single-site laparoscopic colectomy with complete mesocolic excision for colon cancer: a prospective case–control comparison - Takemasa, Ichiro (Springer US, 2013)
BACKGROUND: Single-site laparoscopic colectomy (SLC) is an emerging concept that, compared with conventional multiport laparoscopic colectomy (MLC), yields reduced postoperative pain and improved cosmesis. Complete mesocolic excision (CME) is a novel concept for colon cancer surgery that provides improved oncologic outcomes; however, there are no reports of SLC with CME. We conducted a prospective case–control study to evaluate the feasibility and safety of SLC with CME for colon cancer. METHODS: Prospectively collected data of patients with stage I-III colon cancer who underwent SLC (n = 150) or MLC (n = 150) between June 2008 and March 2012 were analyzed. Patients who underwent SLC were, in terms of clinical characteristics and tumor location, matched as closely as possible with those undergoing MLC. Within each group, patients were classified as having right-sided (n = 69 in each group) or left-sided (n = 81 in each group) colon cancer, and short-term outcomes were compared between the two procedures overall and per side. RESULTS: Overall perioperative outcomes, including operation time, blood loss, number of lymph nodes harvested, length of the resected specimen, and complications, were similar between the two procedures, whereas postoperative pain was significantly lower with SLC. Operation time for right-sided SLC was significantly shortened. SLC with CME was completed successfully in 94 % (65/69) of right-sided cases and in 88 % (71/81) of left-sided cases. Conversion rates were 1.4 % (1/69) and 1.1 % (1/81), respectively. The umbilical scars were nearly invisible 3 months after the procedure, and most patients reported being quite satisfied with the cosmetic outcomes. CONCLUSIONS: SLC with CME for colon cancer is feasible when performed by experienced surgeons in selected patients. Excellent cosmesis and reduced postoperative pain as well as oncologic clearance can be expected. A large-scale, prospective, randomized, controlled trial should be conducted to confirm the superiority of this procedure over MLC with CME.